MEMAHAMI POTENSI EKONOMI, IKLIM INVESTASI DAN PEMBANGUNAN EKONOMI JAWA TIMUR - Didin Fatihudin (UMSurabaya Publishing, 2008)
One of the goals of economic development is economic growth. Potential local economy, innovation and investment climate can affect local economic growth. East Java Province has 38 districts / cities have a chance at better economic growth. Economic development, economic growth plus the change (change), changes in per capita income residents, public health, and public education. Otda Act can be used as a basis for stimulating local economic development in East Java. The results KPPOD, USAID & AF (2007) the investment climate must be created and the desired investor / entrepreneur; the simplification and licensing system, reduction of charges that overlap, transparency of licensing fees, legal certainty and security and availability of infrastructure. The investor and the government of East Java can work together in economic development towards the welfare of society. Keyword: economic potential, investment climate, economic growth, economic development.